Penerapan Kualitas Pelayanan Publik Di Kantor Kelurahan Sawagumu Distrik Sorong Utara - Utami, Fira; Dwi, Fiki Febrian; Ode, Firman (Al-Khidmah : Jurnal Pengabdian dan Pendampingan Masyarakat, 2022)
This research aims to determine the quality of public services in the sawagumu sub-district office, sorong utara district. At the same time, this research can also provide benefits as a solution that can improve the quality of public services. The type of research used is qualitative research. The data source used is secondary data. The number of informants was 4 people. Data collection was carried out using observation techniques. The results of this research indicate that the quality of public services at the sawagumu Electric sorong utara sub-district office is of poor quality when viewed from several indicators of the main dimensions of the quality of public services according to Parasuraman (2012): only in the physical appearance (tangible) dimension such as office facilities which are still lacking. adequate.